PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT SAHABAT JAYA SUKSES ABADI DI KOTA TANGERANG - Candra Edom Sibagariang; Shela Indah Savitri (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of work motivation and work environment on employee job satisfaction at PT Sahabat Jaya Sukses Abadi in Tangerang City. The method used is quantitative. The sampling technique used saturated sampling, namely 82 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work motivation has a significant effect on employee job satisfaction with a coefficient of determination value of 51.7% and the hypothesis test obtained t count > t table or (9.252 > 1.990). The work environment has a significant effect on employee job satisfaction with a coefficient of determination value of 39.2% and hypothesis testing obtained t count > t table or (7.189 > 1.990). Work motivation and work environment simultaneously have a significant effect on employee job satisfaction with the regression equation Y = 8.129 + 0.488X1 + 0.306X2. The coefficient of determination value is 57.9% while the remaining 42.1% is influenced by the coefficient of determination of all variables. Hypothesis testing obtained a calculated F value > F table or (54.217 > 2.720).